Sizzle : a novel - Garwood, Julie (Ballantine Books, 2009)
After she unwittingly captures a shocking crime on camera, a rash of mysterious, treacherous incidents convince Lyra Prescott that she's trapped in a sinister scenario headed for a violent ending. As the noose of deadly intrigue tightens around her, she turns to her best friend, Sidney Buchanan, whose connections bring dauntless and devilishly handsome FBI agent Sam Kincaid into Lyra's running scared life.